BIOATIVIDADE DE PLANTAS PARA O CONTROLE DE PARASITOS: ESTUDO DE BIOPROSPECÇÃO PARA CONSERVAÇÃO DA VEGETAÇÃO DE RESTINGA. - ARAUJO, Ana Cássia Medeiros (2018)
Parasites cause great losses to livestock in the production of ruminants, especially the nematode Haemonchus contortus and the tick Rhipicephalus microplus in tropical countries. Conventional control measures of these organisms are increasingly ineffective, making the development of new strategies imminent. Investigation of vegetal resources for this purpose has obtained satisfactory results, however plant species from endangered environments are few explored in these bioprospecting studies. In this context, the objective of this work was to evaluate the antiparasitic potential of plant extracts from restinga on H. contortus and R. microplus larvae using two different approaches to the selection of the species to be investigated. In the first approach, pre-established criteria (vegetative data) were used for the selection of 19 plant species from a restinga of the Brazilian northeast, located in State of Maranhão (02° 28'23"S, 044° 03'13.8"W), whose leaves were collected and used in the production of hydroethanolic extracts. Initially, these extracts were diluted in 2% methanol at a unique concentration of 1.200 μg/mL and tested in vitro by larval exsheathment inhibition assays on H. contortus larvae. Then, the extracts that showed efficiency equal or greater than 50% were submitted to new inhibition tests at concentrations of 1200, 600, 300, 150 and 75 μg/mL, diluted in 2% methanol. For each treatment, the inhibitory concentrations (IC50) were calculated in the GraphPad Prism 6.0 software, with a 95% confidence interval (95% CI). Eight extracts had an inhibitory effect greater than 50% in the initial screening. In the serial dilution, Terminalia lucida was distinguished with the lowest inhibitory concentration (IC50=53 μg/mL), followed by Conocarpus erectus (IC50=340 μg/mL), Indigofera microcarpa (IC50=351 μg/mL) and Paullinia pinnata (IC50=368 μg/mL). In the second approach, a restinga plant species (Ipomoea imperati) was selected with reports of empirical use in the control of parasitic diseases of veterinary importance for investigation of in vitro efficacy on R. microplus and H. contortus. Hydroethanolic extracts from the leaves and stolon of I. imperati were analyzed by chromatographic and spectroscopic techniques for the detection of secondary metabolites. In addition, these extracts were evaluated in vitro in larval immersion tests against R. microplus using concentrations ranging from 5.0 to 25.0 mg/mL diluted in 70% ethanol; and in larval exsheathment inhibition assays against H. contortus at concentrations of 1.2, 0.6, 0.3, 0.15, 0.07 mg/mL, diluted in 2% methanol. The efficiency of the extracts was demonstrated in each test, respectively, by calculations of lethal concentration (LC50) and inhibitory concentration (IC50). The extracts of I. imperati showed no relevant activity on R. microplus. There was a significant activity only for the extract of I. imperati leaves on H. contortus larvae, whose inhibitory effect was IC50=220 μg/mL. The presence of substances such as procyanidins, kaempferol, isoquercitrin, and rutin possibly contributed to the anthelmintic effect observed for this extract. The results obtained demonstrate that the restinga contains plant species with promising potential in the larval control of H. contortus.